Foreign direct investment in Central and Eastern Europe: An assessment of the current situation - Rolf Alter; Frédéric Wehrlé (Intereconomics, 1993)
Foreign direct investment is an important catalyst for the economic changes in transition economies offering host countries external resources, technology, management, and access to foreign markets. It is therefore high on the public policy agenda in the transition economies of Central and Eastern Europe and the newly independent states of the former Soviet Union and figures prominently among assistance activities at the bilateral and multilateral level. This article analyses the legal and institutional framework and the economic performance of foreign direct investment in fourteen European economies in transition at the beginning of 1993.
Keywords: 330; Foreign Direct Investment